MEMAHAMI MAKNA MITSAQAN GHALIZHAN DALAM AL QUR’AN: Respon terhadap Problematika Hukum Pernikahan di Indonesia - Siswanto (TAFAKKUR : Jurnal Ilmu Al-Qur'an dan Tafsir, 2021)
For Muslims, marriage is not just a demand for physical and spiritual needs as living beings, but more than that, marriage is a medium to perfect their religion. The dimension of worship is very thick in marriage, and there are many evidences/nash from both the Qur'an and hadith that discuss about marriage. In the Qur'an Surah An-Nisa verse 21, Allah said that marriage is kind of mitsaqan ghalidzan, that is a strong and great agreement not only between men and women and their families but also with Allah SWT. Marriage problems are growing from time to time and lead to high divorce rates from year to year, shows that the meaning of marriage is only understood as akad/agreement of handover.  Therefore, this paper discusses the importance of understanding about the meaning of mitsaqan ghalidzan so that Muslims will understand more about purpose and meaning of marriage, so that they can better prepare themselves to carry out a real marriage as their nature for humans.